Ultraprecise Off-Axis Atom Localization With Hybrid Fields - Jia, Ning; Zhao, Xing-Dong; Qi, Wen-Rong; Qian, Jing (Frontiers in Physics, 2022)
Atom localization enables a high-precision imaging of the atomic position, which has provided vast applications in fundamental and applied science. In the present work, we propose a scheme for realizing two-dimensional off-axis atom localization in a three-level Λ system. Benefiting from the use of a hybrid coupling field, which consists of one Gaussian beam and one Laguerre–Gaussian beam, our scheme shows that the atoms can be localized at arbitrary position with high spatial resolution. Considering realistic experimental parameters, our numerical simulation predicts that the atoms can be precisely localized with a spatial resolution of ∼200 nm in the range of a radial distance of a few micrometers to the beam core. Our results provide a more flexible way to localize atoms in a two-dimensional system, possibly paving one-step closer to the nanometer scale atom lithography and ultraprecise microscopy.